“Research Usually Sits on Shelves, Through the Play It Was Shared.” Co-producing Knowledge Through Post-show Discussions of Research-Based Theatre - Lewando Hundt, Gillian; Stuttaford, Maria Clasina; Bryanston, Claudette; Harrison, Christine (Frontiers in Sociology, 2019)
This is a critical analysis of the co-production of knowledge on health care with members of the public attending two research-based plays theatre that were followed by post show discussions with expert panellists. Passing On was developed from the findings of a qualitative research study of family decision making towards the end of life. Cracked explored help seeking pathways for young people experiencing psychosis in families of different ethnicities developed from a research study on this topic. The analysis provides critical reflections on the immediate, post-performance impact of research-based theatre as a strategy to encourage the co-production of knowledge beyond delivery of the performance itself. The plays were developed through partnership working from interview transcripts and joint workshops with academics, users and theatre practitioners (writers, director, actors). Post-show discussions with expert panels were held after each performance to widen participation of the public in the co-production of knowledge to enhance the impact of completed research and stimulate debate. These discussions were audio-recorded and the audience were asked to complete post-show feedback forms. Audience members were researchers, service providers, service users, and carers. This is an analysis of the co-production of knowledge using the feedback forms and transcripts of the post-show discussions. The analysis showed evidence of impact and reflective co-production of knowledge through dialogues that occurred between the audience members, the members of the panel, and the audience and the panel. The discussions covered policy and practice, personal experiences, and theatre making. The post-show discussions led the public to critically discuss issues with the panel and other audience members thus widening participation in the co-production of knowledge. The feedback forms gave information on the audience demographics and what people took away with them. Research based theatre with post-show discussions and evaluation forms is a strategy for widening participation and engagement with health research, through the co-production of knowledge.